2018
DOI: 10.1519/jsc.0000000000002249
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Effort Performance Is Reduced 24 Hours After Acute Dehydration in Mixed Martial Arts Athletes

Abstract: Barley, OR, Iredale, F, Chapman, DW, Hopper, A, and Abbiss, C. Repeat effort performance is reduced 24 hours after acute dehydration in mixed martial arts athletes. J Strength Cond Res 32(9): 2555-2561, 2018-This study sought to determine the influence of acute dehydration on physical performance and physiology in mixed martial arts (MMA). Mixed martial arts athletes (n = 14; age: 23 ± 4 years) completed in a randomized counterbalanced order a dehydration protocol, (DHY: 3-hour cycling at 60 W in 40° C to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 35 publications
2
64
2
1
Order By: Relevance
“…Ad libitum fluid and food consumption resulted in body mass, serum osmolality and haematocrit returning to baseline, however, urine osmolality and USG did not (Table 1 ). These results are similar to those reported previously in research examining acute dehydration in combat athletes ( Barley et al, 2017b ) and indicate the complexity of assessing dehydration and the limitations of using a single (or even multiple) measure of hydration status ( Armstrong, 2007 ). Nevertheless, and of significant practical importance, acute dehydration followed by a rehydration period has been found to impair exercise performance even when several markers of hydration have returned to baseline ( Barley et al, 2017b ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Ad libitum fluid and food consumption resulted in body mass, serum osmolality and haematocrit returning to baseline, however, urine osmolality and USG did not (Table 1 ). These results are similar to those reported previously in research examining acute dehydration in combat athletes ( Barley et al, 2017b ) and indicate the complexity of assessing dehydration and the limitations of using a single (or even multiple) measure of hydration status ( Armstrong, 2007 ). Nevertheless, and of significant practical importance, acute dehydration followed by a rehydration period has been found to impair exercise performance even when several markers of hydration have returned to baseline ( Barley et al, 2017b ).…”
Section: Discussionsupporting
confidence: 87%
“…The method of how dehydration is induced may also be of some importance, as it can be induced using exercise (actively) or by using environmental stress at rest (passively) ( Cheuvront and Kenefick, 2014 ). The negative effects of both active and passive dehydration have also been found to persist even following rehydration, with researchers reporting impairments in repeat-effort capacity ( Barley et al, 2017b ), sports-specific skills ( Baker et al, 2007 ), mood ( Hall and Lane, 2001 ) and cognitive function ( Choma et al, 1998 ) for up to 5 h, and in some cases 24 h, despite ad libitum rehydration. Such findings have substantial implications for athletes in sports with weight classifications (e.g., combat sports), as athletes often attempt to rapidly lose and regain body mass prior to being weighed for competition, with athletes reporting losing 3–5% of their body mass rapidly before being weighed for competition ( Barley et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…greater amount compared with BJJ (P<0.001) ( Table 3). In most 239 combat sports, it was reported that the majority of weight lost in 240 the 24 h before weigh-in was recovered prior to competition and 241 the majority of weight lost was typically regained 7 days 242 following weigh-in ( The present study sought to investigate the strategies used for tasks, 6,12,17 or at least no increase in competitive success. 24,25 We 315 also provide further evidence that weight loss practices in MMA 316 may be more extreme than other combat sports 6 with MMA 317 reporting significantly greater weight loss than other combat 318 sports within two weeks and 24 h of weighing-in (Table 3).…”
mentioning
confidence: 99%
“…These findings conflict with previous research indicating that 335 even when provided with 24 h of ad libitum fluid/food intake 336 athletes may not be adequately rehydrating. 2,12 Clearly, further 337 research is needed to assess the recovery strategies and their 338 efficacy in combat sports following weigh-ins.…”
mentioning
confidence: 99%